2018
DOI: 10.1002/chem.201804369
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Strategy towards Enhanced Performance of the Lithium–Sulfur Battery and its Fading Mechanism

Abstract: To fulfil the potentialo fL i-S batteries( LSBs) with high energy density and low cost, multiple challenges need to be addressed simultaneously.M ost research in LSBs has been focused on the sulfur cathode design, although the performance is also known to be sensitivet oo ther parameters such as binder, currentc ollector,s eparator,l ithium anode, and electrolyte. Here, an integrated LSB system based on the understanding of the different roles of binder, current collector, and separator is developed. By using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 68 publications
(188 reference statements)
0
8
0
Order By: Relevance
“…Accordingly, numerous related articles have been reported. [1][2][3][4][5][6][7][8][9][10][11][12] Various methods have been adopted to improve the low electronic and ionic conductivities and poor cycle performance of sulfur. Initially, the researchers found that using porous carbon as a carrier of sulfur can signicantly improve the performance of lithium-sulfur batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, numerous related articles have been reported. [1][2][3][4][5][6][7][8][9][10][11][12] Various methods have been adopted to improve the low electronic and ionic conductivities and poor cycle performance of sulfur. Initially, the researchers found that using porous carbon as a carrier of sulfur can signicantly improve the performance of lithium-sulfur batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The highfrequency semicircle represents the charge-transfer resistance (R ct ) of the sulfur cathode, and the low-frequency sloping lines reect the lithium-ion diffusion resistance within the electrodes. 43 From correlative equivalent circuit models, the cell with the S-NACC-50%-coated separator showed a R ct value of 9.9 U, which is lower than that of the cell with the P-AB-coated separator (26.4 U) and conventional separator (38.0 U). It could be guessed that the charge-transfer resistance would be reduced by the addition of SPS and NACC, which could decrease the kinetics impedance, and the result is corresponding to the cycle performance tests.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, the presence of nanoparticles, high specific surface area, and porous structure increases the electrical conductivity and performance of electrochemical properties [ 49 ]. Other researchers coated carbon paper or carbon-coated aluminium foil by acid-CMC (CA-CMC)-based nanocomposite to produce an electrode (cathode) for LISB [ 50 ]. The authors made a slurry of CA-CMC, MWCNT, S, and Ketjenblack (KB) by grinding, heating, and mixing with water for the coating.…”
Section: Cellulose-based Bionanocomposites For Batteriesmentioning
confidence: 99%